Notes on Dun an Iardhard, a Broch near Dunvegan, excavated by Countess Vincent Baillet de Latour, Uiginish Lodge, Skye (Proceedings of the Society of Antiquaries of Scotland, 1915)
In contrast with many of the duns in Skye this example is only slight elevated. The interior was completely filled by fallen masonry all of which was removed. The main entrance is flanked by projecting masonry, and guard chambers either side. The diameter is 174 feet and the surviving height of the broch is 29 feet. Artefacts included a necklace of amber beads, a steatite armlet, a quernstone, a whetstone, animal bone, decorated pottery and a lot of iron slag.